Brand evangelists’ expectations: consumption decisions towards digital corporate social responsibility communication - Santoso, Nobertus Ribut; Negoro, Sherly Hindra (Universitas Padjadjaran, 2025)
Background: Digital Corporate Social Responsibility (CSR) communication could effectively influence stakeholders’ decisions. Purpose: This study explores how the expectations of millennials as brand evangelists towards digital CSR communication contribute to purchasing behavior. Methods: Using a qualitative approach, this study examines Indonesian millennials’ perceptions and attitudes toward CSR activities communicated by Indonesian unicorn companies on Instagram. The data were collected through interviews with 15 Indonesian millennials who actively use Instagram and follow the official account(s) of at least one Indonesian unicorn company. Results: The findings reveal that millennials share positive experiences and support CSR initiatives through Instagram, with communication conveyed transparently and effectively. This demographic’s digital savviness improves expectations for CSR initiatives, which, in turn, influence consumption choices through partnerships with Micro, Small, and Medium Enterprises (MSMEs) and through content that promotes their business sustainability. Conclusion: Indonesian unicorn companies adopt strategic digital CSR communications to meet the heightened expectations of Indonesian millennial consumers, who serve as brand evangelists, supporting, inspiring, and recommending their products. Implications: By aligning CSR initiatives with their brand and sharing them through digital channels, Indonesian unicorn companies can build consumer awareness, trust, engagement, and loyalty, ultimately promoting positive consumption decisions through rational and ethical actions that contribute to societal progress.